Bioinformatics-based identification of differentiated expressed microRNA in esophageal squamous cell carcinoma - Lau, King Wai; Zeng, Haikang; Liang, Hengrui; Su, Xi; Ma, Jieling; Wen, Shuai; Li, Jin (Translational Cancer Research, 2018)
Background: Although numerous studies have identified and observed altered expression of microRNAs in esophageal squamous cell carcinoma (ESCC), only a limited number of miRNAs were reported up to date, partially due to the limitation of sample size (less than or equal to 100 pair of paired samples). Thus, we performed a comprehensive analysis to improve the ability to detect miRNA expressed differentially in ESCC. Methods: The study datasets were systematically searched and downloaded from public available databases including European Bioinformatics Institute (EMBL-EBI), ArrayExpress and Gene Expression Omnibus (GEO) database. Only datasets derived from ESCC patients were further screened and quality assessed using R programming language with ArrayExpress package. A total of 4 datasets covering 349 ESCC cases and 326 normal esophageal tissue samples (NE) were included in this study. Results: The analytic results showed that a total of 108 miRNAs were differentially expressed in esophageal cancer, of which 48 were up-regulated and 60 were down-regulated compared with the adjacent normal esophageal tissues. Moreover, we successfully identified 9 novel differentially expressed miRNAs that have not been discovered to associate with esophageal cancer in the previous studies. We also predicted top 5 potential target genes of these novel miRNAs. Conclusions: The bioinformatics based analysis summarized the current differential expression of miRNA in ESCC, and exploring unknown miRNA target genes provides guidance for discovering the new biomarkers of ESCC.